Effect Of Leadership Style On Employee Performance - Kifayat Ali Larik; Abdul Karim Lashari (NAROTAMA UNIVERSITY, Indonesia, 2022)
In this study it comes under the observation that there is a big effect on employees through Leadership skills. These effective practices make stronger to organization and another aspect with this observation is to clearly justify the effect of styles in a different way like Democratic, autocratic, and participative style on employees for enhancing their performance. The main objective with great Guidance it was analyzed that obviously autocratic style has much effect on employee performance inside the organization. On other side the way of participative is quietly good for further efficiency raising up. This study is based on qualitative approach, whereas Secondary research is on prior behalf. The reason behind this study is to have further discussion widely on employees’ performance as the readers can get bunch of knowledge about it. In secondary research it will be added to putt data via reports general information magazines and general Journal. Making widely valuable to this article it came to know that there is greater impact of Leadership style on employees acts the roe of behavior and its performance. Democratic style is highly useful beneficial for employees at all times while the participation style is also beneficial for employee’s performance on a long-term duration Few further recommendations are under the discussion in this thesis.